2021
DOI: 10.1002/psp.2436
|View full text |Cite
|
Sign up to set email alerts
|

Brexit, acculturative stress and mental health among EU citizens in Scotland

Abstract: The ‘Brexit’ referendum represents a hostile shift in the United Kingdom's acculturative context. With its remain majority and pro‐migration political discourse, Scotland appears less hostile than the rest of the United Kingdom. We explored whether and how Brexit affected the mental health of European Union citizens living in Scotland. Thirty EU citizens took part in seven focus groups. Participants reported three main sources of acculturative stress: uncertainty, feelings of rejection and experiences of loss.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This is corroborated by the similarly strong increase in UK migration flows and naturalisations in other EU/EFTA countries as well as by related existing research (Benson, 2019). Third, while this study focuses on the impact of uncertainty as a motivational factor for migration, it is clear from our findings that there are other psychological effects of Brexit that might also influence migration decisions, such as stigmatisation (Frost, 2020; Teodorowski et al, 2021), discrimination (Rzepnikowska, 2019), alienation (Ranta & Nancheva, 2019; Teodorowski et al, 2021), or impaired mental health (Teodorowski et al, 2021). At the same time, anticipation of such factors could again exacerbate the salience of uncertainty (Auer & Ruedin, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…This is corroborated by the similarly strong increase in UK migration flows and naturalisations in other EU/EFTA countries as well as by related existing research (Benson, 2019). Third, while this study focuses on the impact of uncertainty as a motivational factor for migration, it is clear from our findings that there are other psychological effects of Brexit that might also influence migration decisions, such as stigmatisation (Frost, 2020; Teodorowski et al, 2021), discrimination (Rzepnikowska, 2019), alienation (Ranta & Nancheva, 2019; Teodorowski et al, 2021), or impaired mental health (Teodorowski et al, 2021). At the same time, anticipation of such factors could again exacerbate the salience of uncertainty (Auer & Ruedin, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…experience of racism [ 39 ]) as a challenge for them to be involved. This is despite the fact that there is evidence that Brexit impacted on the integration of European Union citizens in the UK [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those who already were living in the UK had to apply for settled status and their right to remain. Many Polish people living in the UK experienced racism and discrimination [39] and Brexit as a political event negatively influenced Poles' mental health and wellbeing [40]. South Asians consist of multiple national groups: India, Pakistan, Bangladesh, Nepal, Bhutan, the Maldives and Sri Lanka.…”
Section: Participantsmentioning
confidence: 99%
“…Research by Teodorowski et al (2021) has shown that these actions helped to mitigate feelings of rejection experienced by EU residents after the referendum. Participants in almost all their focus groups commented approvingly on the letter they received from the First Minister, which reassured them that they were ‘welcome’, ‘wanted’ and ‘needed’ in Scotland and several participants contrasted Scotland favourably with other parts of the United Kingdom.…”
Section: Post‐devolution Initiativesmentioning
confidence: 99%